Pengembangan Modul Praktikum Berbasis Kecerdasan Buatan (AI) Terintegrasi STEM untuk Efisiensi Waktu dan Biaya di SMPSK Regina Pacis - Anna Julita Foa; Lidia Langley Teang Teang; Ni Wayan Suparmi (SMA Negeri 1 Bangkinang Kota, 2026)
This research aims to formulate and test a framework for developing a practicum module based on STEM-integrated Artificial Intelligence (AI) which is specifically designed to overcome the main obstacles to conventional practicum, namely high costs, safety risks and time constraints. STEM practicum is crucial for developing 21st century skills (problem solving, critical thinking) in junior high school students, but its implementation at SMPSK Regina Pacis Bajawa is hampered by limited facilities and infrastructure. The research method uses Research and Development (R&D) by adapting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The novelty of the research lies in the integration of AI for operational efficiency through two main features: (1) AI Interactive Simulation for elimination of physical material requirements and risks, and (2) Intelligent Auto-grading System for accelerated evaluation and providing instant feedback. The limitations of this research lie in the limited trial scale (only at SMPSK Regina Pacis Bajawa) and not measuring the long-term impact on knowledge retention and skill transfer to real situations. In addition, this AI module is very dependent on the availability of school digital infrastructure (computers and internet connections) which may be an obstacle in some areas.